Evaluation of the cholinomimetic actions of trimethylsulfonium, a compound present in the midgut gland of the sea hare Aplysia brasiliana (Gastropoda, Opisthobranchia) - Kerchove,C.M. (2002)
Trimethylsulfonium, a compound present in the midgut gland of the sea hare Aplysia brasiliana, negatively modulates vagal response, indicating a probable ability to inhibit cholinergic responses. In the present study, the pharmacological profile of trimethylsulfonium was characterized on muscarinic and nicotinic acetylcholine receptors. In rat jejunum the contractile response induced by trimethylsulfonium (pD2 = 2.46 ± 0.12 and maximal response = 2.14 ± 0.32 g) was not antagonized competitively by atropine. The maximal response (Emax) to trimethylsulfonium was diminished in the presence of increasing doses of atropine (P<0.05), suggesting that trimethylsulfonium-induced contraction was not related to muscarinic stimulation, but might be caused by acetylcholine release due to presynaptic stimulation. Trimethylsulfonium displaced [³H]-quinuclidinyl benzilate from rat cortex membranes with a low affinity (Ki = 0.5 mM). Furthermore, it caused contraction of frog rectus abdominis muscles (pD2 = 2.70 ± 0.06 and Emax = 4.16 ± 0.9 g), which was competitively antagonized by d-tubocurarine (1, 3 or 10 µM) with a pA2 of 5.79, suggesting a positive interaction with nicotinic receptors. In fact, trimethylsulfonium displaced [³H]-nicotine from rat diaphragm muscle membranes with a Ki of 27.1 µM. These results suggest that trimethylsulfonium acts as an agonist on nicotinic receptors, and thus contracts frog skeletal rectus abdominis muscle and rat jejunum smooth muscle via stimulation of postjunctional and neuronal prejunctional nicotinic cholinoreceptors, respectively.